2020
DOI: 10.1007/s43032-020-00363-8
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Measuring Vitamin D Serum Levels in Women with Uterine Fibroids

Abstract: Uterine fibroids (UFs) are benign tumors originating from smooth muscle cells and are considered a common pathology that affects numerous women which is a notable socio-economic problem. Several UF risk factors have been identified including black race, obesity, and vitamin D deficiency. Vitamin D is steroid compound with pleiotropic effects on the human body. Vitamin D deficiency is a major public health concern worldwide. Several studies have shown that the majority of UF patients experienced hypovitaminosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 101 publications
(173 reference statements)
1
17
2
Order By: Relevance
“…Overall, the relationship between vitamin D and uterine fibroid metabolism has been characterized. Recently, our research team proposed a preliminary clinical instruction of 25(OH)D measurements and vitamin D supplementation that may be useful for clinicians involved in treating patients with uterine fibroids ( 374 ).…”
Section: Key Pathways Contributing To Uterine Fibroids Formationmentioning
confidence: 99%
“…Overall, the relationship between vitamin D and uterine fibroid metabolism has been characterized. Recently, our research team proposed a preliminary clinical instruction of 25(OH)D measurements and vitamin D supplementation that may be useful for clinicians involved in treating patients with uterine fibroids ( 374 ).…”
Section: Key Pathways Contributing To Uterine Fibroids Formationmentioning
confidence: 99%
“…In a later study, Wise identified single-nucleotide polymorphisms in genes involved in vitamin D metabolism that were significantly associated with UFs [ 121 ]. It has also been shown African American women have lower serum vitamin D levels than white Americans, which could explain the increased risk of UFs [ 122 ]. Al Hendy et al observed that vitamin D could be a potent antiestrogenic agent that reduces the expression of sex steroid receptors and consequently the risk of UFs [ 123 ].…”
Section: Uterine Fibroidsmentioning
confidence: 99%
“…Al Hendy et al observed that vitamin D could be a potent antiestrogenic agent that reduces the expression of sex steroid receptors and consequently the risk of UFs [ 123 ]. Vitamin D has been shown to be a potent antitumor agent inhibiting UF cell proliferation and decreasing UF size in in vivo animal models as well as several clinical trials [ 122 , 124 , 125 ]. Mechanistically, vitamin D might exert its anti-UF effects via induction of DNA repair genes and amelioration of DNA damage both in UF cells and in myometrial cells at risk of developing UFs [ 126 , 127 , 128 ].…”
Section: Uterine Fibroidsmentioning
confidence: 99%
“…Vitamin D also has its specific type of receptorvitamin D receptor (VDR). Binding with VDR, vitamin D mediates its pleiotropic functions through steroid transcriptional mechanisms 123,124 .…”
Section: Endocrine-disrupting Chemicals and Inflammation In The Pathogenesis Of Ufsmentioning
confidence: 99%